Control sustentable del vector del HLB en la Agricultura Familiar en Argentina, Uruguay, Paraguay y Bolivia - Giancola, Silvana Ines; Aguirre, Maximo Raul Alcides; Di Masi, Susana Noemi; Bravo, Gonzalo Carlos; Molina, Nestor Albino; Alderete Salas, Susana Ines; Beltran, Victor Manuel (2020)
Póster